Influence of Social Media Marketing, Perceived Value and Brand Trust on Willingness to Pay for Green Food Packaging - Sinchai, Tanaporn; Namwat, Thatphong (Connexion: Journal of Humanities and Social Sciences, 2025)
This study aims to (1) examine the relationships among social media marketing, perceived environmental value, brand trust, and consumers’ willingness to pay (WTP) for green food packaging, and (2) investigate the mediating roles of perceived environmental value and brand trust between social media marketing and WTP for the packaging. Data were collected from 320 respondents who had prior experience in buying green food packaging. A non-probability sampling approach was employed for data collection. Quota sampling was then used to ensure proportional representation of regional populations in Thailand. Data were collected using an online questionnaire and analyzed through descriptive statistics and structural equation modeling (SEM). The findings show that the proposed WTP model demonstrates a good fit with the empirical data. Social media marketing does not exert a direct effect on WTP (p > 0.05), however, it significantly affects perceived environmental value and brand trust. Both perceived environmental value and brand trust positively influence WTP, with brand trust emerging as the most influential factor (Total Effect = 0.878). Furthermore, perceived environmental value acts as a partial mediator between social media marketing and WTP, whereas brand trust provides full mediation effect.